Synergistic actuation performance of artificial fern muscle with a double nanocarbon structure - Chae-Lin Park; Byeonghwa Goh; Keon Jung Kim; Seongjae Oh; Dongseok Suh; Young-Chul Song; Hyun Kim; Eun Sung Kim; Habeom Lee; Dong Wook Lee; Joonmyung Choi; Shi Hyeong Kim (Materials Today Advances, 2024)
Electrochemically powered carbon nanotube (CNT) yarn muscles are of increasing interest because of their advantageous features as artificial muscles. They are light, and have high electrical properties, mechanical strength, and chemical stability. Twist-based CNT yarn muscles show superior actuation performance: 30 times the work capacity and 85 times the power density of natural muscles. Despite achieving these high performances, there is still potential for performance improvement because their twisted structure is not fully utilized. In particular, designing a cross-sectional structure that allows ions to freely enter and exit the twisted structure of the yarn muscle is necessary. Here, we propose highly enhanced artificial muscles with high chemical stability that consist of only nanocarbon materials of carbon nanoscroll (CNS) and twisted CNT yarns. The CNS/CNT yarn muscles (CCYM) can improve the ion accessibility and utilization of the twist structure. The maximum contractile stroke, work capacity, power density, and energy conversion efficiency of the CCYM were 20.11%, 2.26 J g−1, 0.53 W g−1, and 3.39%, which are 1.4-, 1.4-, 4.8, and 4.3 times that of the pristine CNT yarn muscles, respectively. The effects of CNS on CCYM were confirmed by experimental and theoretical analyses. Additionally, in a solid electrolyte, which opens up new application possibilities, the CCYM demonstrates high actuation performance (16.38%) with very low input energy.